Experimental Application of Thermoelectric Devices to the Rankine Cycle. (August 2015) - Siviter, J.; Montecucco, A.; Knox, A.
Abstract: Thermal plants operating on the Rankine cycle are by far the most common method of global electrical power generation. The Rankine cycle, first developed in the late 19 th century, continues to this day to be one of the most important practical implementations of a heat engine. Innovation and enhancement of this cycle continue and today's emphasis is directed towards reduced carbon emissions from the combustion of fossil fuel as well as improvement of the absolute cycle efficiency. This paper presents a technique to increase in the Rankine cycle efficiency through reducing the waste heat rejected during the condensation phase by use of a thermoelectric heat pump. Firstly, this work derives a theoretical statement of the required Coefficient of Performance for viable economic operation. This is followed by an experimental investigation to determine if the calculated performance is available using today's thermoelectric technology.